Strategic HRM practices : perspectives of Malaysian and Japanese owned companies in Malaysia - Abang Ekhsan, Abang Othman (Global Business and Management Research, 2009)
Purpose - This study examines the applications and processes of one of the key distinctive features of strategic HRM, i.e. integration of HRM functions with business/corporate strategy and two key HRM functions, recruitment and selection and training and development.